Islamic Turn in Malay Historiography: Bustān al-Salāṭīn of 17th Century Aceh - Burhanudin, Jajat (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2021)
Bustān al-Salāṭīn by Nūr al-Dīn al-Ranīrī (d. 1659) is a leading Malay text on Islamic history. Written in the 17th century in Aceh, one chapter of the Bustān was dedicated to the history of Aceh. This paper discusses how the Bustān described the formation of the sultanate, the rulers who were in power, their political behaviour, and the methods of statecraft they tried to establish. The text shared the emerging intellectual discourse in 17th Century Aceh, in which al-Ranīrī’s reform of Muslims’ religious practices to uphold sharī‘ah-based principles gained its prominence. With the support of his patron, Iskandar Thani (1636-1641), al-Ranīrī’s Islamizing efforts for Aceh are reflected in the Bustān. This paper argues that the Islamic ideals and terms found in the Bustān signify the history of Aceh and profile the patron, which sets Bustān apart from previous Malay texts of historical writing.